Problem Based Learning in Engineering Course in Malaysia - Hadibarata, Tony; Hidayat, Topik; Kwabena, James (Tecno Scientifica Publisher, 2023)
Problem-based learning (PBL) is an effective educational approach that promotes critical thinking, collaboration, and creativity. The study aimed to review an implementation of PBL in engineering course in Malaysia. PBL has been shown to be effective in engaging students in the learning process by presenting them with complex, open-ended problems that require critical thinking and creativity to solve. Through this process, students develop their critical thinking skills, including their ability to analyze information, evaluate arguments, and make sound judgments. PBL also helps students to develop their problem-solving skills, which are essential in the real world. Despite its benefits, implementing PBL in the classroom can also have some challenges and limitations. It can be time-consuming, difficult to assess, challenging to implement in large classes, and may not be suitable for all students. Thus, careful planning and preparation are required before implementing PBL in a university setting. In an engineering course, PBL provides students with opportunities to develop their critical thinking and problem-solving skills, as well as to enhance their collaboration and communication abilities. It also allows students to see the relevance of the knowledge and skills they are learning and to take ownership of their learning. Therefore, implementing PBL in a university requires identifying appropriate learning objectives and designing a problem or scenario that aligns with those objectives. The problem or scenario should be complex and open-ended, requiring students to draw on knowledge and skills from multiple subject areas. The implementation of PBL should also involve ongoing evaluation and refinement to ensure its effectiveness.